Sedimentary Characteristics and Genetic Mechanisms of Non-Evaporitic Gypsum in a Half-Graben Basin: A Case Study from the Zhanhua Sag, Bohai Bay Basin, China - Muxin Cai; Jianguo Zhang; Zaixing Jiang; Junliang Li; Tao Meng; Peng Liu; Chao Jiang (Journal of Marine Science and Engineering, 2025)
Gypsum and salt rocks have been proven to act as seals for abundant oil and gas reserves on a global scale, with significant potential for hydrocarbon preservation and evolution. Notably, the sedimentary dynamics of non-evaporitic gypsum in terrestrial half-graben basins remain underexplored, particularly regarding its genetic link to hydrocarbon accumulation in interbedded mudstones. This study is based on the Zhanhua Sag, in which thick-layered gypsum rocks with dark mudstone are deposited. The gypsum crystals show the intermittent deposition characteristics. The cumulative thickness of the gypsum-containing section reaches a maximum of over 110 m. The spatial distribution of gypsum thickness correlates strongly with the location of deep-seated faults. The strontium and sulfur isotopes of gypsum indicate deep hydrothermal fluids as mineral sources, and negative oxygen isotope excursions also suggest that gypsum layers precipitated in situ from hot brine. Total organic carbon and Rock-Eval data indicate that the deep-lake gypsum rock system has excellent hydrocarbon potential, especially in the mudstone interlayers. This study developed a depositional model of deep-lake gypsum rocks with thermal brine genesis in half-graben basins. The gypsum-bearing system is rich in mudstone interlayers. These gypsum–mudstone interbeds represent promising targets for shale oil exploration after the initial breakthrough during the extraction process. These insights provide a theoretical framework for understanding gypsum-related petroleum systems in half-graben basins across the globe, offering guidance for hydrocarbon exploration in analogous sedimentary environments.